COMPARISON OF LIFESTYLE OF INGRESSING AND CONCLUDING ACADEMICS OF A CENTRAL UNIVERSITY OF GOIANIA - Araújo, Elizangela Ribeiro de; Benedito, Josélia Carneiro; Lima, Soraia Oliveira; Magalhães, Fabricio Galdino; Sá Filho, Alberto Souza (International Journal of Movement Science and Rehabilitation, 2020)
The aim of this study was to analyze the lifestyle profile of new academics and senior students in health courses at a faculty in central GoiÃ¢nia. The instrument used for data collection was the Pentacle â€œWellbeingâ€ Questionnaire developed and approved by Nahas, Barros and Francalacci (2000). The survey consisted of 193 participants who answered fifteen closed questions related to five domains: nutrition, physical activity, preventive behavior, social relationship and stress control. Data analysis was performed from mean Â± standard, where ANOVA 3 x 2 compared the beginners and graduates averages, and between courses, adopting the significance level of P <0.05. In a general analysis, the results show regular indices for all components. The Physical Activity component was superior among the aspiring graduates of Physical Education professionals, while the Preventive Behavior showed superior behavior in Nursing graduates. Some components showed significant differences between new academics and seniors (physical activity, preventive behavior, and relationship). Thus, it is concluded that the answers differ partially from the hypothesis initially postulated, since it was expected that graduates would have a higher prevalence of favorable health promotion behaviors, since they acquired theoretical and practical information during the course about the importance of healthy habits.